Risk Factor of Lost to Follow-up Treatment in drug-sensitive pulmonary TB patients - Rina Sari Mardia; Bintang Yinke Magdalena Sinaga; Parluhutan Siagian; Taufik Ashar (CV. Inara, 2025)
Background: Loss to follow-up (LTFU) treatment remains a critical challenge in tuberculosis control in Indonesia, accounting for approximately 50% of treatment failure cases among pulmonary TB patients. Objectives: To identify independent predictors of LTFU among drug-sensitive TB (DS-TB) patients in Medan, Indonesia. Methods: This cross-sectional analytical study enrolled 100 DS-TB patients (40 with LTFU, 60 treatment-completed) from two hospitals. Purposive sampling technique was employed. Data were collected using validated questionnaires assessing sociodemographic characteristics, patient perspective toward TB treatment, social support (using MSPSS scale), and healthcare services quality. Bivariate analysis used chi-square and Fisher's exact tests; multivariate analysis employed multiple logistic regression. Statistical significance was set at p < 0.05. Results: Multivariate analysis identified two independent predictors of LTFU: social support (odds ratio 128.632; 95% confidence interval 13.809 to 1,198.216; p < 0.001) and treatment perspective (odds ratio 25.415; 95% confidence interval 5.569 to 115.985; p < 0.001). Low to moderate social support was the most dominant risk factor, conferring approximately 128.7 times greater odds of treatment discontinuation compared to high social support. Poor treatment perspective was the second dominant predictor, with 90% of LTFU patients demonstrating negative perspectives. Conclusion: Poor treatment perspective and low to moderate social support are significantly associated with LTFU treatment discontinuation in DS-TB patients. Psychosocial interventions addressing these factors should be prioritized in TB control programs to improve treatment completion rates and achieve WHO treatment success targets.